A rare case of bronze diabetes in a patient with thalassemia - Sharma, Karan V.; Khandhedia, Parth B.; Sharma, Vijay H. (International Journal of Advances in Medicine, 2022)
Secondary haemochromatosis (also known as bronze diabetes) is a perilous medical condition that can occur as a complication of frequent blood transfusions. Thalassemia major which occurs due to a decrease in the beta globulin chain can lead to severe anemia, extramedullary hematopoiesis and splenomegaly. Because of this, the affected patients required continuous blood transfusions throughout their life and as a consequence, it may lead to iron overload. A 26-year-old male presented with a complaint of darkening skin, joint pain and fever. He was a known case of thalassemia major and was undergoing blood transfusions three times a week. Further laboratory findings revealed decreased hemoglobin, abnormal liver function tests and increased blood glucose levels. The patient was managed with IV insulin and chelation therapy. The patient responded to treatment and was better on subsequent follow-up. The diagnostic and therapeutic challenges along with the epidemiological data emphasize the need of raising the awareness of physicians to this devastating condition.